Основні напрями вдосконалення законодавства щодо забезпечення політичних прав громадян України - Гончарова, І. А.; Honcharova, I. A. (Вісник Запорізького національного університету. Сер.: Юрид. науки. – 2014. – № 4, ч. 1. – С. 78-85, 2014)
Наголошено, що політичні права людини й громадянина властиві здебільшого громадянам України. Вони являють собою забезпечену законом і публічною владою можливість людини брати участь у громадсько-політичному житті держави та здійсненні державної влади, а також є неодмінною умовою функціонування всіх інших видів прав, оскільки утворюють органічну основу системи демократії та визначають природу держави як засіб контролю за владою. Підкреслено, що удосконалення законодавства про адміністративні проступки потребує вдосконалення системи державного управління, приведення норм адміністративного права у відповідність до положень Конституції України, забезпечення реалізації прав і свобод громадян у сфері державного управління, їх охорони й захисту адміністративно-правовими засобами.

Political rights of a person and a citizen are secured by the law and public authorities’ ability of a person to actively participate in the exercise of the state power. The political rights of citizens include the rights on associations of citizens in political parties and public organizations, opportunity to participate in political life of the state, satisfaction of political, economic, social, cultural and other interests, as well as the right to participate in public administration. Political rights are only recognized to citizens and cover the relations between a citizen and the state. Current legislation consolidates liability for violating political rights, but there are some issues concerning their realization. This leads to violations of established procedures and deprives citizens the possibility to realize their rights at the appropriate level. There are political rights of citizens, which did not find their guaranteeing by the norms of administrative liability. Thus, the right of the citizens on free assembly, rallies, marches and demonstrations require strengthening of legal protection. It should be noted that the improvement of the legislation on administrative offenses in this area requires improvement in the public administration sphere. To enhance the protection of the rights and freedoms of citizens, there is also a need to improve the system of norms that reinforce the administrative offenses, as a number of rights and freedoms are beyond the legal protection. Besides, it is necessary to consolidate officials’ liability in the Code of Ukraine about Administrative Offences for obstructing the implementation of political rights of the citizens. Apparent “imbalance” of rights, duties and liability of the participants of legal relations arising in this area negatively affect on the functioning of the mechanism of political rights realization. It is known that rallies and demonstrations are extremely dangerous instrument of democracy, so unreasoned, and the more malicious their use may result to negative and unpredictable consequences. To determine the fact whether participants of meetings, rallies, demonstrations, pickets are or are not beyond the scope of the law one requires a more clear and complete legal basis.

Отмечено, что политические права человека и гражданина присущи преимущественно гражданам Украины. Они являют собой обеспеченную законом и публичной властью возможность человека участвовать в общественно-политической жизни государства и осуществлении государственной власти, а также являются непременным условием функционирования всех других видов прав, поскольку образуют органическую основу системы демократии и определяют природу государства как средство контроля за властью. Подчеркнуто, что усовершенствование законодательства об административных проступках требует усовершенствования системы государственного управления, приведения норм административного права в соответствие с положениями Конституции Украины, обеспечения реализации прав и свобод граждан в сфере государственного управления, их охраны и защиты административно-правовыми средствами.
The main areas of improving legislation guaranteeing political rights of Ukrainian citizens
Основные направления усовершенствования законодательства по обеспечению политических прав граждан Украины
Гончарова, І. А. Основні напрями вдосконалення законодавства щодо забезпечення політичних прав громадян України / Гончарова І. А. // Вісник Запорізького національного університету. Сер.: Юрид. науки. – 2014. – № 4, ч. 1. – С. 78-85.
Keywords: Конституційне право. Constitutional Law. Конституционное право; Наукові публікації. Scientific publications. Научные публикации; Адміністративне право та процес. Administrative Law and Procedure. Административное право и процесс; Україна. Ukraine. Украина; політичні права громадян; political rights of citizens; политические права граждан; удосконалення законодавства; improvement of legislation; усовершенствование законодательства; адміністративно-правові засоби; administrative and legal means; административно-правовые средства